Topical Issues of the Theory and Practice of Import Substitution in the Russian Federation - Belobragin, Victor Yakovlevich; Burak, Petr Iosifovich; Zvorykina, Tatiana Ivanovna; Rostanets, Victor Grigorievich; Magomedov, Shamil Magomedovich (International Journal of Economics and Financial Issues, 2016)
The article analyzes the status and prospects of development of the activities of governing bodies and industries in the Russian Federation in the field of import substitution. It is shown that after the crisis of 1998, the first significant measures to reduce the volume of imports by development of domestic production were taken in Russia. Then, the process of import substitution slowed. This problem greatly exacerbated due to the introduction of economic sanctions by the West and by the Russian counter-measures to restrict imports, mainly food. In this connection, dependence of a number of important sectors of the economy on imports and the lack of measures taken at all levels of management of the economy to improve the efficiency of import substitution are shown. One reason for this situation is weak development of scientific and methodological foundations of this economic phenomenon. The elements of the theory of import substitution and practical recommendations on the use of program-target method for planning work on import substitution through the development and implementation of targeted programs at the federal, regional and enterprise levels were proposed. Keywords: Import substitution, import replacement, competitiveness, quality, targeted programs. JEL Classifications: B41, D24, F51, L10, L16